2016
DOI: 10.5114/fn.2016.64815
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of biochemical and volumetric biomarkers to assess the risk of conversion of mild cognitive impairment to Alzheimer’s disease

Abstract: A b s t r a c t Introduction: The aim of our study was to evaluate the usefulness of several biomarkers in predicting the conversion of mild cognitive impairment (MCI) to Alzheimer's disease (AD): β-amyloid and tau proteins in cerebrospinal fluid and the volumetric evaluation of brain structures including the hippocampus in magnetic resonance imaging (MRI). Material and methods: MRI of the brain with the volumetric assessment of hippocampus, entorhinal cortex, posterior cingulate gyrus, parahippocampal gyrus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In 2018, the National Institute on Aging and the Alzheimer's Association presented the research framework [44] that similarly as the Erlangen Score Algorithm [19,28] did not officially include apoE as AD biomarker, probably due to contradicting results regarding its function in animal models [4,24] and diverse data on apoE level in human AD pathology [27]. There are studies performed on peripheral blood drawn from AD patients, demonstrating elevated [26,62,66], unchanged [11,32,39,46,53,57,61] and reduced apoE levels [18,20,29,30,36,52,55,60,68] in [72].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the National Institute on Aging and the Alzheimer's Association presented the research framework [44] that similarly as the Erlangen Score Algorithm [19,28] did not officially include apoE as AD biomarker, probably due to contradicting results regarding its function in animal models [4,24] and diverse data on apoE level in human AD pathology [27]. There are studies performed on peripheral blood drawn from AD patients, demonstrating elevated [26,62,66], unchanged [11,32,39,46,53,57,61] and reduced apoE levels [18,20,29,30,36,52,55,60,68] in [72].…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by deficits in attention, executive function, working memory and information processing ( Sampath et al, 2017 ), Mild Cognitive Impairment (MCI) is considered to be a critical stage intermediate period between normal aging and dementia. Data show that 20–30% of patients who were diagnosed as MCI will develop into dementia like Alzheimer’s disease (AD) in 2 years ( Alzheimer’s Association, 2016 ; Nesteruk et al, 2016 ; Pena-Altamira et al, 2017 ). What are the earliest origins of AD?…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies analyzing significant biomarkers associated with MCI-to-AD conversion, but the results have been inconsistent. Some studies have demonstrated that different biomarkers, including hippocampal volume, the CSF tau/Aβ-42 ratio, tau proteins and Aβ levels, which had great sensitivity up to 88.9% and specificity up to 96.8%, and the combined assessment outperformed single biomarker assessments 34,35 . Other studies have also shown that absent APOE4 alleles may predict MCI stability for at least 3 years 36 , plasma homocysteine and serum brain-derived neurotrophic factor may predict MCI-to-AD conversion in patients with the APOE ε4 genotype 37 , and plasma beta-secretase 1 activity is significantly increased in MCI converters 38 .…”
Section: Discussionmentioning
confidence: 99%